Prove that, tan3theta - tan2theta - tantheta= tan3theta.tan2theta.tantheta
Answers
Answered by
3
Answer:
I am taking theta as a
tan3a - tan2a - tana
As tanb - tanc = (tan (b-c)) (1+tanb tanc)
take b =3a and c = 2a
tan 3a- tan 2a = tan(3a-2a) (1+tan3a tan2a)
= tan a ( 1+ tan 3a tan 2a)
Now, come back to question
tan 3a - tan2a -tan a
= tan a (1+ tan 3a tan2a ) -tan a
=tan a (1+ tan3a tan2a -1)
= tan a tan3a tan 2a
hence proved
#answerwithquality #BAL
Answered by
0
Answer:
we have to solve the equation,
tanθ + tan2θ + tan3θ = tanθ.tan2θ.tan3θ
we know,
tan(A + B + C) = (tanA + tanB + tanC - tanA.tanB. tanC)/(1 - tanA.tanB - tanB.tanC - tanC.tanA)
tan(6θ) = tan(θ + 2θ + 3θ) = ( tanθ + tan2θ + tan3θ - tanθ.tan2θ.tan3θ)/(1 - tanθ.tan2θ - tan2θ.tan3θ - tan3θ.tanθ)
here , if we assume , tan(6θ) = 0
then, tanθ + tan2θ + tan3θ = tanθ.tan2θ.tan3θ
hence, tan(6θ) = 0 = tan(π)
or, 6θ = nπ
or, θ = nπ/6 , where n ∈ Z
Similar questions